The Complex Relationship between Online Social Feedback and Well-Being - Mirko Duradoni; Veronica Spadoni; Mustafa Can Gursesli; Elena Pratelli; Andrea Guazzini (Human Behavior and Emerging Technologies)
With the growing prevalence of online social interactions, it is crucial to understand how the social dimension affects well-being. This study investigates the relationship between the Need for Online Social Feedback (NfOSF) and individuals’ well-being, considering the moderating role of perceived online reputation. A total of 1398 participants, predominantly female, aged 14 to 61, completed an online questionnaire. The results revealed an M-shaped pattern, indicating that both dissatisfaction and excessive satisfaction with online reputation were associated with lower well-being. For those dissatisfied with their reputation, a high desire for social feedback correlated with reduced well-being, as validation from the social environment, was lacking. Similarly, individuals with fully satisfying reputations experienced frustration in their pursuit of online social feedback. In this case, the “Fame” dimension of the NfOSF scale exhibited a negative association with well-being, highlighting the impact of grandiose expectations. The findings underscore the subjective nature of this relationship, emphasizing the role of individual characteristics and social context.